Marketing methods and political promotion to shape the mental image - Maarouf, Dr. Abdelkader; altayf, yasin (Journal of Tikrit university for humanities - مجلة جامعة تكريت للعلوم الانسانية; Vol 25 No 5 (2018): Journal of Tikrit University for HumanitiesDO - 10.25130/hum.v25i5.534, 2019)
The research aims at finding out the most prominent methods of political marketing which electional and political compaigns use and finding out the most important methods, which the media use for forming political mental image for audience. The study includes three chapters. The first chapter deals with the frame work of the research. The second chapter deals with the methods and concept of political marketing, while the third chapter deals with the concept political promotion and the formation of mental image.